Video by Artists 2 - Town, Elke (Toronto : Art Metropole, 1986)
Sherman, Tom ; London, Barbara ; Marshall, Stuart ; vom Bruch, Klaus ; Barry, Judith ; Bellour, Raymond ; General Idea ; Fargier, Jean-Paul ; Graham, Dan ; Friedel, Helmut ; Gale, Peggy ; Campbell, Colin ; Dercon, Chris ; etc.
Engels
boek